2019
DOI: 10.1017/s030500091800051x
|View full text |Cite
|
Sign up to set email alerts
|

Processing of unfamiliar accents in monolingual and bilingual children: effects of type and amount of accent experience

Abstract: Substantial individual differences exist in regard to type and amount of experience with variable speech resulting from foreign or regional accents. Whereas prior experience helps with processing familiar accents, research on how experience with accented speech affects processing of unfamiliar accents is inconclusive, ranging from perceptual benefits to processing disadvantages. We examined how experience with accented speech modulates mono- and bilingual children's (mean age: 9;10) ease of speech comprehensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 79 publications
1
29
0
Order By: Relevance
“…In the repetition task, participants transcribed or repeated utterances (in three speech contexts) that were presented to them along with a static photograph of a given talker (six photographs). To control for inter-speaker variability in the three speech contexts, one speaker for each accent (Standard German, Korean-accented German, Palatinate regional accent of German) was used [for more details on the recordings, see 52 ], and two different versions of each recording were created by minor changes to the effective vocal-tract lengths (see also [ 19 , 53 ]). This allowed for a given experimental list to contain each accent paired with each ethnicity (e.g., the foreign-accented talker in voice version 1 was paired with an Asian prime, while the same foreign-accented talker in voice version 2 was paired with a white European prime).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the repetition task, participants transcribed or repeated utterances (in three speech contexts) that were presented to them along with a static photograph of a given talker (six photographs). To control for inter-speaker variability in the three speech contexts, one speaker for each accent (Standard German, Korean-accented German, Palatinate regional accent of German) was used [for more details on the recordings, see 52 ], and two different versions of each recording were created by minor changes to the effective vocal-tract lengths (see also [ 19 , 53 ]). This allowed for a given experimental list to contain each accent paired with each ethnicity (e.g., the foreign-accented talker in voice version 1 was paired with an Asian prime, while the same foreign-accented talker in voice version 2 was paired with a white European prime).…”
Section: Methodsmentioning
confidence: 99%
“…The women were matched with respect to age, hairstyle, hair length, and ratings of attractiveness and trustworthiness. Acoustic stimuli consisted of 36 short utterances in German, with a total length of 193 words (mean utterance word length 5.3, SD = 0.9; e.g., Das Bild gibt dem Jungen einen Stuhl ‘the picture gives the boy a chair’; taken from [ 52 ]). These were spoken by three female talkers, each representing one speech context: Standard German, Korean-accented German, and Palatinate German.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, in the Hong Kong situation, English as a foreign language may be more like an academic skill compared to the more colloquial native Cantonese. Hence, the academic vocabulary is typically much more prominent in English than Cantonese, whereas the reverse is true for the colloquial vocabulary (Levy, Konieczny, & Hanulíková, 2019). If twinning impacts on learning through family interactional factors, the Cantonese academic vocabulary and the English colloquial vocabulary would be the least affected.…”
Section: Discussionmentioning
confidence: 99%
“…This means that we cannot rule out a possibility that the advantage for multi-dialect children in the experimental group does not stem from their ability to cope better with accent variability, but rather is attributed to their general capacity to learn words (in which case, the home dialect exposure would facilitate performance in both groups). Although research in older children suggest that dialectal experience enhance the ability to cope better with accent input (Levy et al, 2019), the alternative explanation needs further investigation (currently examined in our lab). accents and generalize knowledge to other speakers and accents), ten months later they experience more difficulties in learning words in multi-accent inputas compared to toddlers raised in bi-dialectal familiessuggesting that multi-accent variability might pose initial difficulties for word learning in toddlers with no prior accent experience; yet they seem to 'catch up' with their bi-dialectal peers after being familiarized with the story and/or the accents.…”
Section: Role Of Familiarity With Accent-variability On Word Learning In Multi-accent Inputmentioning
confidence: 94%
“…Research in older children has shown that familiarity with regional accents improves adaptation to unfamiliar accents (Levy et al, 2019). to 0.025 and Bayes Factor analyses were used to examine the strength of evidence presented by our data.…”
mentioning
confidence: 99%